2018
DOI: 10.1002/ar.23864
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Innervation of the Human Soft Palate

Abstract: The human soft palate plays an important role in respiration, swallowing, and speech. These motor activities depend on reflexes mediated by sensory nerve endings. To date, the details of human sensory innervation to the soft palate have not been demonstrated. In this study, eight adult human whole-mount (soft palate-tongue-pharynx-larynx-upper esophagus) specimens were obtained from autopsy. Each specimen was bisected in the midline, forming two equal and symmetrical halves. Eight hemi-specimens were processed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…We found the sensory nerves were significantly decreased in CIH-induced rat. Sensory inputs from the upper airway play an important role in initiation of various physiological reflexes and in feedback control of motor activities [27]. Clinical testing of the soft palate and pharyngeal mucosa in OSA patients by cold sensory testing showed upper airway sensory impairment [28].…”
Section: Discussionmentioning
confidence: 99%
“…We found the sensory nerves were significantly decreased in CIH-induced rat. Sensory inputs from the upper airway play an important role in initiation of various physiological reflexes and in feedback control of motor activities [27]. Clinical testing of the soft palate and pharyngeal mucosa in OSA patients by cold sensory testing showed upper airway sensory impairment [28].…”
Section: Discussionmentioning
confidence: 99%
“…The human soft palate is one of key structures involved in repetitive obstruction and breathing interference during sleep [ 3 ]. OSA patients with IH mainly result from a pathological progression followed by the collapse of the soft palate.…”
Section: Discussionmentioning
confidence: 99%
“…This disorder is characterized by the collapse of the soft palate in the upper airway, resulting in chronic intermittent hypoxia (IH) during sleep [ 2 ]. Several studies have demonstrated that the collapse of the soft palate might result from pathophysiological changes in inflammatory infiltration, an increase in mucosa thickness and abnormal afferent nerve endings [ 3 ]. It was also reported that soft palates from OSA patients were characterized by mucous gland hypertrophy, focal atrophy of muscle fibers and extensive edema of the lamina propria [ 4 ].…”
mentioning
confidence: 99%